The role of corporate governance in moderating the influence of financial distress on earnings management - Widayawati, Eny; Saroh, Siti; Trianti, Khoiriyah; Anastuti, Karina Utami (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2025)
Purpose – This research is to analyze the influence of financial distress on earnings management and analyze the role of Good Corporate Governance as proxied by independent commissioners in moderating the influence of financial distress on earnings management in banking companies on the Indonesia Stock Exchange for the 2018-2024 period.Design/methodology/approach – The sample in this study was determined using purposive sampling. The sample size is 150 company annual reports. Data collection uses documentation. Data analysis uses multiple regression and moderated regression analysis (MRA).Findings – Financial distress is proven to influence earnings manage¬ment. This means that when a company faces financial difficulties, management will usually carry out earnings management to cover up the financial difficulties faced so it looks good in the eyes of stakeholders. With the implementation of independent commissioners as supervisors and givers of advice who come from outside the company, it will weaken the relationship between financial distress and earnings management. This means that earnings management will go down along with the imple¬mentation of good corporate governance as proxied by independ¬ent commissioners.Research limitations/implications – The contribution presented to the independent variable on the profit-related variable is in a small group, so that there are suggestions for further studies to add related variables to this external study area and apply other sectors for future studies.Practical implications – This research provides practical benefits to banking company management to avoid earnings management practices by implementing independent commissioners.Originality/value – Previous research linking the influence of financial distress on earnings management with independent commissioner moderation has not been widely conducted and the results are still varied.